POLITICAL ADMINISTRATION IN THE STATE OF KARAKHANYS (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the administrative system of the Kara-Khanid State, which existed in the 9th–12th centuries. It provides information about the khan’s authority, central and local administrative bodies, as well as military and bureaucratic positions that played a significant role in governance. The article explains the duties and roles of officials such as viziers, hojibs, yugrishes, jandors, and salokhdors. It also examines changes in the judicial system following the adoption of Islam as the state religion, including the activities of qazis, muftis, and the imam-mavrat divan. Furthermore, the article highlights that the Kara-Khanid administrative system was formed based on Turkic traditions and Islamic governance principles and that it was crucial for maintaining state stability.